College Algebra
posted by Patrick:) .
Solve the logarithmic equation for x.
log(base 3)(x+6)  log(base 3)(x+1)=1
urgent! help!
Respond to this Question
Similar Questions

check!
here is the question: log5(x4)= log7x solve for x. These are just base 10 logs. log100 = 2 This equation has the same format as log 40 = log (2x20) Since both sides have log base 10, you divide by log base 10 and end up with 5(x4) … 
Math  Logarithmic
log_5[log_4(log_3(x))] = 1 log_5 = log with the base of 5 log_4 = log with the base of 4 log_3 = log with the base of 3 Answer: 3^1024 Too many logs in one equation. . .I don't know how to solve it 
Math
Help with these problems would be greatly appreciated: 1.Find the definite integral of dx/(x(1+ln(x))from e^6 to 1. 2. Solve for x in terms of k for log[2,x^6)+log[2,x^10=k. (its log base 2) 3.Solve log base 3(log base 3, x)=2 
math(Please help)
1) use the properties of logarithms to simplify the logarithmic expression. log base 10 (9/300) log  log 300 log 9 = 2 log 3 log 300 = log 3 + log 100 = log 3+2 I just do not know how to put these together now! 
College Algebra
Solve the logarithmic equation. Express your solutions in exact form only. Please show all of your work. log base 6 (64x^3+1)log base 6 (4x+1)=1 
Trig
log base b 64  log base b 16 = log base 4 16 solve for the variable.. i got to the part as far as: (log 4/log b) = 2 now i m stuck at how i can isolate the b. plz help! 
Algebra 2
Explain the difference between log base b (mn) and ( log base b of m)(log base b of n). Are they equivalent? 
Algebra
In the logarithmic expression . . . log(base 4) 8 , how does the base 4 become base 2? 
Advanced Functions/ Precalculus Log
1. Evaluate 4^(log base4 64) + 10^(log100) 2. Write 1+log(base2)x^3 as a single logarithm 3. Write log(base b)√(x^3 y z^6) 4. Solve log(base 2)xlog(base 2)6=log(base 2)5+2log(base 2)3 5. Solve 3^(2x) = 9(81^x) 6. Solve 3^(2x)=7^(3x1). … 
precalc
Solve: round to the thousandths if necessary! 1) 4^3/4x+5 = 12 2) log(x1) + log x = log 6 3) 2log(base 4) 5  log(base 4) x + log(base 4) 3  log(base 4) 7 = 1/2